Assessing the impact of construction waste reduction on selected projects in Ireland. Issue 3 (31st July 2018) - Gottsche, Jan; Kelly, Mark
Abstract : The construction sector generates approximately 9% of gross domestic product (GDP) in the European Union (EU), providing over 18 million direct jobs, demonstrating the role it plays in economic output and development. However, construction activities have a direct impact on resource efficiency with over half of all extracted materials and energy consumption and a third of water consumption linked to construction and use of buildings in the EU. In addition, the sector generates about one-third of all waste. This connection between construction output and resource use needs to be addressed. This study presents results identifying cost savings and reduced environmental impact associated with the implementation of waste-reduction initiatives during the construction of five healthcare and educational projects in Ireland. Total savings of €68 448 were estimated across all five projects. This represented 49% of the total expenditure on waste management on-site and a saving of 4·2% of the assumed average profit margin. It was also calculated that the implemented initiatives resulted in savings of 128 t of carbon dioxide. It was found that simple quick-win waste-reduction measures can increase profit margins and reduce environmental impact.